Fracture fixation in polytraumatized patients—From an interdisciplinary early total/appropriate care to the safe definitive surgery concept - Kalbas, Yannik; Heining, Sandro-Michael; Kaiser, Anne; Klingebiel, Felix Karl-Ludwig; Pfeifer, Roman; Wanner, Guido A.; Pape, Hans-Christoph (Frontiers in Medicine, 2024)
Strategies for the timing of fracture fixation in polytrauma patients have undergone changes, as resuscitation and patient assessment have improved. Namely, the criteria for damage control had become available and more precise parameters have been found to determine those patients that can safely undergo primary definitive fixation of major fractures. Our surrent recommendations are supported by objective and data based criteria, and development groups (867 patients (23.6%) of which were treated prior to 2001 (before introduction of damage control techniques, 1262 (45.1%) patients belonged to the years 2003 to 2008 (incorporation of damage control techniques for major fractures (Group 2)), and 1539 (54.9%) were treated after 2009 (changes in nonsurgical management, eg. transfusion and fluid management guidelines))(Development group, Pape et al. Injury, 2019). The validation group compared the existing scores in a separate analysis (Halvazichadeh et al. Plos One, 2020).This review summarizes the pertinent stages of development of a "safe definitive surgery" concept and provides an update on parameters used to select the patients accordingly.